CANDI MUARA JAMBI SEBAGAI SUMBER PEMBELAJARAN SEJARAH LOKAL JAMBI DALAM PERIODISASI HINDU – BUDHA - Siti Heidi Karmela, Nur Agustiningsih (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2017)
AbstracThe purpose of this research is to describe the role of Muara Jambi enshrinement site as a Jambi local history learning and explain the noble values that’s taken from Muara Jambi enshrinement site. The research method used is historical method, which is a process of testing and critically analyzing past events, with stages starting from heuristics, criticism, interpretation, historiography. In more detail this research begins with topic selection, the collection of written materials that are relevant to the chosen theme, doing the criticism of removing the facts that are not authentic so that it is able to lift the facts authentically and credibly. Furthermore to conclude and collect the various facts obtained and arrange them into a story or a meaningful presentation. This research is expected to have an important meaning especially in the study of Jambi local history in Hindu Buddhist period, and become a literary source in the form of scientific journals containing information about one of the historical sites (Muara Jambi Temple) in the form of artifacts, as well as a promotion event of Jambi History at national level.Keywords : Site, Temple, Muara Jambi